Messenger RNA in differentiating muscle cells—my experience in François Gros’ lab in the 1970s and 80s - Buckingham, Margaret (Comptes Rendus Biologies, 2023)
I joined François Gros’ laboratory as a postdoc at the end of 1971 and continued working with him as a research scientist until 1987, when I became an independent group leader at the Institut Pasteur. In the early 1970s, it was the beginning of research in his lab on muscle cell differentiation, as a model eukaryotic system for studying mRNAs and gene regulation. In this article, I recount our work on myogenesis and mention the other research themes in his lab and the people concerned. I remained in close contact with François and pay tribute to him as a major figure in French science and as my personal mentor who provided me with constant support.